Автомобильные дороги примеры проектирования: учебное пособие - Андреев О. В. Олег Владимирович; Бабков В. Ф. Валерий Федорович; Бим-Бад М. И. Макс Исаакович; Дивочкин О. А. Олег Александрович; Порожняков Владимир Сергеевич (Москва, Транспорт, 1983)
Авт. указаны на обороте тит. л.